The Global Financial Crisis and Economic Growth: An Analysis of the East Asian Economies - Fang Yin; Xiao Hong; Lin Yao (Pancasila International Journal of Applied Social Science, 2023)
Along with more its integrated economy in middle globalization era, crisis finances that occur in a country can with easy spread to countries other and become a global financial disaster in period time which short. On incident sort of this, very strong economic fundamentals important for maintain something country from effect crisis which "infectious". As proof, because it is fundamental economy Which fragile And lack of credibility government, East Asian economies can attacked with easy by crisis on year 1997 so market confidence is deteriorating. however , Asia This East has Study Lots from incident on year 1997 is so it can be prove its resilience in face crisis finance global that hit in 2008 with increase fundamentals the economy as well as credibility para policy makers. This paper started with theory about growth economy And crisis finance. Furthermore, empirically test so far where crisis finance on year 1997 And 2008 affected Asian economies East with use data panel econometrics. The evidence shows that, though second crisis has give impact bad on economy East Asia, crisis wave 2008 relatively No more critical than crisis year 1997. Finally, study this also provides an explanation more carry on about how economy Asia East has succeeded in minimizing the impact of the crisis global on year 2008.